GAD1 expression and its methylation as indicators of malignant behavior in thymic epithelial tumors - Soejima, Shiho (Oncol Lett, 2021)
Thymic epithelial tumors (TETs) comprise thymomas and thymic carcinoma (TC). TC has more aggressive features and a poorer prognosis than thymomas. Genetic and epigenetic alterations in thymomas and TC have been investigated in an attempt to identify novel target molecules for TC. In the present study, genome-wide screening was performed on aberrantly methylated CpG islands in thymomas and TC, and the glutamate decarboxylase 1 gene (GAD1) was identified as the 4th significantly hypermethylated CpG island in TC compared with thymomas. GAD1 catalyzes the production of γ-aminobutyric acid from L-glutamic acid. GAD1 expression is abundant in the brain but rare in other tissues, including the thymus. A total of 73 thymomas and 17 TC tissues were obtained from 90 patients who underwent surgery or biopsy at Tokushima University Hospital between 1990 and 2017. DNA methylation was examined by bisulfite pyrosequencing, and the mRNA and protein expression levels of GAD1 were analyzed using reverse transcription-quantitative PCR and immunohistochemistry, respectively. The DNA methylation levels of GAD1 were significantly higher in TC tissues than in the normal thymus and thymoma tissues, and GAD1 methylation exhibited high sensitivity and specificity for discriminating between TC and thymoma. The mRNA and protein expression levels of GAD1 were significantly higher in TC tissues than in thymomas. Patients with TET with high GAD1 DNA hypermethylation and high mRNA and protein expression levels had significantly shorter relapse-free survival rates than those with low levels. In conclusion, significantly more epigenetic alterations were observed in TC tissues compared with in thymomas, which may contribute to the clinical features and prognosis of patients.